The Role of γδ T Cells in Systemic Lupus Erythematosus - Meng Wu; Jinhua Yang; Xiaofeng Li; Junwei Chen (Journal of Immunology Research)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by the overproduction of autoantibodies against an array of nuclear and cytoplasmic antigens and affects multiple organs, such as the skin, joints, kidneys, and neuronal tissues. T cells have been recognized as important players in the development of SLE due to their functions in cytokine secretion, antigen presentation, and supporting B cells for antibody production. γδ T cells are a minor population of T cells that play important roles in infection and tumor-associated disease. In recent years, the role of γδ T cells in autoimmune diseases has been investigated. In this review, we discussed the role of γδ T cells in the pathogenesis of SLE.